Nrf2/cyclooxygenase 2 signaling in Cr(VI)-induced carcinogenesis - Lei Zhao; Yi-Fang Wang; Andrea Adamcakova-Dodd; Peter S. Thorne; Ranakul Islam; Ke Jian Liu; Fei Chen; Jia Luo; Ling-Zhi Liu (Ecotoxicology and Environmental Safety)
Long-term exposure to hexavalent chromium [Cr(VI)] has been linked to lung cancer, and cyclooxygenase-2 (COX-2) is a well-known inflammatory factor. However, the role and mechanism of COX-2 in Cr(VI)-induced carcinogenesis are not clear yet. To address this question, we employed a mouse model exposed to Cr(VI) through intranasal instillation of particulate zinc chromate (ZnCrO4) for 12 weeks. Metabolomics and RNA-seq assays revealed enhanced activity of the arachidonic acid (AA)/eicosanoid metabolism pathway in lung tissues from mice exposed to Cr(VI). COX-2, the key enzyme of the AA/eicosanoid pathway, was significantly upregulated in Cr(VI)-exposed lung tissues, as well as in the Cr(VI)-induced transformed (Cr-T) cells compared to parental BEAS-2B (B2B) cells. We then employed multidisciplinary in vitro and in vivo functional assays to characterize the role of COX-2 in Cr(VI)-induced lung cancer. The results indicated that COX-2 functioned as an oncogene to promote the malignant transformation of B2B cells and enhance the proliferation, migration, tumor growth, and angiogenesis of Cr-T cells. Nuclear factor E2-related factor-2 (Nrf2) was identified as a transcription factor for COX-2. Nrf2 was upregulated in response to Cr(VI) exposure and contributed to Cr(VI)-induced lung cancers, in part by upregulating COX-2 expression. Moreover, microRNA-379 (miR-379) was found to target COX-2 to inhibit its expression posttranscriptionally. MiR-379 was downregulated in Cr(VI)-exposed lung tissues and Cr-T cells, and ectopic miR-379 expression reduced Cr-T cell viability and migration, with partial reversal upon COX-2 restoration. In summary, our study revealed the oncogenic role of COX-2 and identified two novel regulatory mechanisms for COX-2 overexpression in Cr(VI)-induced carcinogenesis.